Main Agro-Morphological and Biochemical Berry Characteristics of Wild-Grown Sea Buckthorn (Hippophae rhamnoides L. ssp. caucasica Rousi) Genotypes in Turkey - Ilhan, Gülçe; Gundogdu, Muttalip; Karlović, Ksenija; Židovec, Vesna; Vokurka, Aleš; Ercişli, Sezai (Sustainability, 2021)
Sea buckthorn (Hippophae rhamnoides L. ssp. caucasica Rousi) is one of the most important wild edible fruits, grown in Turkey for centuries without any chemical treatments. The plant is extremely resistant to adverse environmental conditions. In this study, the main agro-morphological and biochemical berry traits and, to a lesser extent, other plant morphological traits of 10 sea buckthorn genotypes sampled from the eastern Anatolia (Sivas province) region were assessed. Among the 10 genotypes, five of them presented a shrub growth habit, whereas five of them presented tree growth habit, with leaf area ranging from 2.56 to 4.22 cm2. The majority of genotypes had an oblong berry shape with variable berry skin color ranging from dark orange to orange, light orange, and yellow. The weight of 100 berries varied from 13.85 to 23.87 g, while juice yield and vitamin C content was found to be 44.87–57.15% and 37.45–62.85 mg/100 g fresh berry base, respectively. Soluble solid content (SSC) was in the range of 12.56–14.67%. The genotypes exhibited a great variability in total anthocyanin content (from 9.1 to 38.7 mg/L), with relatively dark-orange sea buckthorn berries containing more anthocyanin than orange, light-orange, and yellow berries. Linoleic acid was the main fatty acid detected in the pulp of sea buckthorn berries, ranging from 24.11% to 36.37%, depending on the genotype. Investigated genotypes proved also to be rich in total phenolic content, showing at the same time great variability in this trait. The results obtained from the relatively limited number of genotypes show promising traits for further valorization of both horticultural and nutritional traits, suggesting potentially even higher variability, if more genotypes are going to be considered in the future.